Improved Rifamycin B Production by Nocardia mediterranei MTCC 14 under Solid-State Fermentation through Process Optimization. (9th October 2014) - Vastrad, Basavaraj M.; Neelagund, Shivayogeshwar E.; Iiger, Sudhir R.; Godbole, Ajeet M.; Kulkarni, Venkatrao
Abstract : Optimization of various production parameters using response surface methodology (RSM) was performed to assess maximum yield of rifamycin B from Nocardia mediterranei MTCC 14. Plackett-Burman design test was applied to determine the significant effects of various production parameters such as glucose, maltose, ribose, galactose, beef extract, peanut meal, ammonium chloride, ammonium sulphate, barbital, pH, and moisture content on production of rifamycin B. Among the eleven variables tested, galactose, ribose, glucose, and pH were found to have significant effect on rifamycin B production. Optimum levels of the significant variables were decided by using a central composite design. The most appropriate condition for production of rifamycin B was found to be a single step production at galactose (8% w/w), ribose (3% w/w), glucose (9% w/w), and pH (7.0). At these optimum production parameters, the maximum yield of rifamycin B obtained experimentally (9.87 g/kgds dry sunflower oil cake) was found to be very close to its predicted value of 10.35 g/kgds dry sunflower oil cake. The mathematical model developed was found to fit greatly with the experimental data of rifamycin B production.